SKRINING AKTIVITAS ANTIBAKTERI FRAKSI EKSTRAK ETANOL KERNEL BIJI BUAH LIMUS (Mangifera foetida Lour.) TERHADAP Staphylococcus aureusDAN Escherichia coli - Nurviana, Vera (Journal of Pharmacopolium, 2018)
Limus (Mangifera foetida Lour.) Is one of the local Indonesian fruits of the anacardiaceae family. Limus contain secondary metabolites that have pharmacological effects, including the kernel waste of the seeds of the fruit. This study aims to determine the antibacterial activity against Staphylococcus aureus and Escherichia coli on the fraction of kernel seed of limus fruits ethanolic extract in invitro using solid diffusion method with positive control Tetracycline HCl. The extraction process was carried out by maceration method, then fractionation was obtained to obtain the fraction of n-hexane, ethyl acetate fraction and water fraction. Based on the result of the research, the fraction of n-hexane, ethyl acetate fraction, and water fraction of kernel ethanol extract limus fruit seed have antibacterial activity against Staphylococcus aureus and Escherichia coli. The highest activity was shown by fraction of ethyl acetate with minimum killing concentration (KBM) to Staphylococcus aureus was 5% with diameter equal to 4,33 Â± 1.17 mm equal to 30,27 Î¼g / mL Tetracycline HCl, and KBM value to Escherichia coli.4% (7.60 Â± 0.14) mm equivalent to 26, 04 Î¼g / mL Tetracycline HCl. Keywords: Antibacterial, Staphylococcus aureus, Escherichia coli, Kernel, M. foetida.